Analysis of Regional Water Availability for Domestic Water Demand (Case Study: Malang Regency) - Dinia Putri; . Perdinan (Agromet, 2018)
The fulfillment of water demands needs to consider climate variability impacts on water availability. A seasonal change from wet to dry may have a negative impact on water availability leading to water scarcity for domestic purposes. Therefore, information on water condition until sub-district level is important. We did water balance approach to analyze water condition especially during dry season in Malang district, East Java for period 2007-2016. Our results showed that several sub-districts faced a serious problem with water deficit condition. During dry season, an increased domestic water demand was not supported by water availability, which caused some villages could not provide basic water for domestic purposes. Further, the research may contribute to support mitigation and adaptation strategy for climate extreme in the region.